Unravelling the anomalous electrical and optical phase-change characteristics in FeTe. (15th June 2016) - Ho, H.W.; Branicio, P.S.; Song, W.D.; Bai, K.; Tan, Teck L.; Ji, R.; Yang, Y.; Yang, P.; Du, Y.H.; Sullivan, M.B.
Abstract: In contrast to conventional phase-change materials we show that amorphous FeTe displays higher electrical conductivity and optical reflectivity than its crystal phase. This anomalous phenomenon is rooted in the delocalization of Te-p electrons in the amorphous phase. Originally existing as localized lone-pairs in the layered-like crystalline structure, Te-p electrons hybridize with empty Fe-d orbitals to generate p-d antibonding states below the Fermi level in the amorphous phase, which shifts up the amorphous phase valence band and results in delocalization of the valence band electrons to account for the concurrent anomalies. The unraveled lone-pair hybridization/dehybridization mechanism presents a paradigm for identifying anomalous phase-change materials. Graphical abstract: